MYTHOLOGIC AND DESTRUCTION OF THE SCIENTIFIC AND ARCHAIC CONSCIOUSNESS (TRAVELING TO SOURCES OF PRESOCRATIC THINKING) - V. B. Okorokov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The purpose of research consists in that: having plunged into depths of primitive consciousness (using the recipe of many thinkers of non-classical philosophy), to reveal contradiction of the European thought (at its sources) in Ancient Greek thought and show resources of mythological thinking on the way of overcoming of these contradictions. Methodology. All methodological installations, using possibilities, borderlines and effects of non-classical consciousness, have appeared insufficiently effective for adequate understanding of essence of the person. The generalised method, which is used by us, leans on deep resources of high-energy consciousness and on decoding of possibilities of anthropological time that it presumes to open new horizons of human existence. Originality. Addressing to modern representations about the changed conditions of consciousness, we have tried to see the historically generated discursive practices of understanding reality by the consciousness (including the historical one). Thus, using the consistently conducted destruction we are aimed at reaching the first sources of consciousness and revealing the deep historical mechanisms of temporal consciousnesses formation (as far as it possible in the modern conditions). Conclusions. It is shown that the use of the basic ideas of Ancient Greek thought leads scientific consciousness to deadlocks of contradictions, which were consistently revealed during subsequent history of philosophy and culture. The analysis of ancient mythological texts allows concluding, that the Greek thought is not a source of modern scientific thought. That is to understand the scientific thought one should address to the more ancient archaic thinking. Thus, to overcome the contradictions of modern scientific and philosophical thought it is necessary to search new alternative (more ancient) sources of understanding of the historical reality, first of all, connected with deepening into ancient (mythological) thought.